A zero-failure accelerated degradation test under ramp–soak–stress loading. (June 2018) - Wanti Srivastava, Preeti; Manisha,
This article deals with the design of optimal ramp–soak–stress accelerated degradation test using Wiener process for modeling degradation paths. In an accelerated degradation test, failure occurs when the performance characteristic crosses the critical value the first time. Accelerated degradation test is incorporated in zero-failure reliability demonstration test to facilitate reduction in the test duration resulting in reduction in the test cost of high-reliability items. The parameters in model are estimated using method of maximum likelihood. The optimum plan consists in finding out optimum number of ramp–soak–stress cycles, optimum number of specimens, optimum stress change point(s), and optimum stress rates by minimizing asymptotic variance of estimate ofqth quantile of the lifetime distribution at use condition subject to the constraint that total testing or experimental cost does not exceed a prespecified budget. An example is given to illustrate the proposed model, and sensitivity analysis is also carried out.